Approximation of Systems with Delay and Algorithms for Modeling Their Stability. - Cherevko, Igor; Tuzyk, Iryna; Ilika, Svitlana; Pertsov, Andriy (My University, 2021)
In this paper, the schemes of approximation of linear systems with delays by spesial systems of ordinary differential equations are considered and the connections between their solutions are investigated. Numerical algorithms for studying the stability of linear stationary systems with delay are constructed and their coefficient regions of stability are modeled.
Keywords: Systems with Delay; Approximation of Systems; Approximation schemes; quasi-polynomial; stability; upper limit of stability; region of stability